Effect of the number of pregnancies on mortality risk in HIV-infected women: a prospective cohort study in rural KwaZulu-Natal, South Africa - Yoo, Hyunsuk; Bärnighausen, Till (Aids and behavior, 2018)
We investigated whether mortality risk increases with the number of full-term pregnancies in HIV-infected women. Our study is based on data from the ACDIS cohort, collected in rural KwaZulu-Natal, South Africa. Mortality risk for different number of pregnancies in HIV-infected women was analyzed using Cox proportional hazards model. The risk of TB or AIDS mortality in HIV-uninfected women did not change with the number of full-term pregnancies, while the corresponding risk increased markedly in HIV-infected women. The risk of TB or AIDS mortality increased 1.48-fold (95% CI 1.25-1.75), 1.76-fold (95% CI 1.45-2.13), and 1.59-fold (95% CI 1.31-1.94) for one, two, and three or more full-term pregnancies compared to none, respectively. Finally, women who are young (age < 26) have greater risk of TB or AIDS mortality compared to women who are old (age ≥ 26), and women residing in rural areas have greater risk compared to women who reside in non-rural areas.
Gesehen am 29.04.2020